Fibroblast Growth Factor 21 Levels Exhibit the Association With Renal Outcomes in Subjects With Type 2 Diabetes Mellitus - Chang, Li-Hsin; Chu, Chia-Huei; Huang, Chin-Chou; Lin, Liang-Yu (Frontiers in Endocrinology, 2022)
Background Whether microalbuminuria predicts renal outcomes in patients with type 2 diabetes mellitus (T2DM) is argued. Fibroblast growth factor 21 (FGF-21) levels were elevated by the pathogenic process of diabetic kidney disease. The purpose of the study was to evaluate the associations of FGF-21 and renal outcomes in subjects with T2DM. Methods Chinese patients with T2DM were enrolled and then observed prospectively, and FGF-21 levels at baseline were measured. The associations of FGF-21 levels and renal composite events, defined by a drop > 30% of eGFR or worsening category of albuminuria, were evaluated using Cox analysis. The appropriate cut-off value of FGF-21 was mapped by the receiver operating characteristic (ROC) curve. Results Among 312 subjects, higher FGF-21 levels were associated with higher risks of renal events in Cox analysis. The area under the curve of FGF-21 levels in the ROC curve was optimal (0.67, p < 0.001), and the cut-off value of 1.40 pg/dl exhibited the best sensitivity (76.2%) and specificity (53.5%). The frequency of renal composite events was higher in subjects with FGF-21 ≥ 1.40 pg/dl than in others (30% vs. 10%, p<0.001 by the log-rank test). The worse renal outcomes predicted by FGF-21 ≥ 1.40 pg/dl were confirmed using the adjustments of Cox sequential models (hazard ratio 2.28, 95% confidence interval 1.23–4.24, p=0.009) and consistent across subjects with different status of baseline characteristics and renal risks. Conclusion FGF-21 levels were proportional to the risks of renal events in broad- spectrum Chinese T2DM subjects, making it a potential biomarker to predict the renal outcomes of T2DM.